Revitalisasi Pelabuhan di Kota Pasuruan, Jawa Timur (Selasar, 2022)
Pasuruan port still mixed between loading and unloading activities, landing fishing activities, transportation, and the settlements. This condition effect on the function of the main port in general. However, through the development of the role and its function in the future, Pasuruan port is a network sea transportation that has the potential to be multiplier effect accelerator for the economic growth of Pasuruan. In the past, Pasuruan was also known as a Bandar Kuno city, which has vital trade infrastructure support in the form of a quite crowded which serves as the commerce causing the activity of the economic sector upstream until downstream helped move dynamically. Pasuruan port in the last 10 years has experienced a significant decline in terms of functions and activities, due to the lack of facilities support the current port activities. Therefore, the need to revitalize the Pasuruan port is expected to restore the glory of Pasuruan port.